Effects of high-pressure homogenization on structural and emulsifying properties of thermally soluble aggregated kidney bean (Phaseolus vulgaris L.) proteins. (October 2021) - Guo, Zengwang; Huang, Zhaoxian; Guo, Yanan; Li, Bailiang; Yu, Wenhua; Zhou, Linyi; Jiang, Lianzhou; Teng, Fei; Wang, Zhongjiang
Abstract: High-pressure homogenization (HPH) can improve the functionalities of food proteins by forming soluble aggregates. This research aimed to determine the effects of thermal aggregation and high-pressure homogenization on the structural and emulsifying properties of kidney bean proteins. Results have shown that the soluble aggregates from heat-treated kidney bean proteins had markedly larger particle sizes and molecular weights than untreated proteins. This demonstrates that heat treatment could expose buried hydrophobic groups and free sulfhydryl groups, leading to SH/SS exchanges between protein molecules. Additionally, the viscosity, emulsifying activity, and emulsion stability of the thermally formed soluble aggregates increased substantially after heat treatment. HPH at a low pressure (30, 60 MPa) promoted the formation of disulfide bonds between molecules by hydrophobic interaction, leading to the formation of protein soluble aggregates. This increased the particle size, molecular weight, apparent viscosity, emulsion activity, and emulsion stability. HPH at high pressures (90, 120 MPa), on the other hand, has been shown to damage protein aggregates and break the disulfide bond, resulting in a decreased aggregate size, molecular weight, emulsion activity, and emulsion stability. Our findings showed that HPH at 60 MPa on thermally soluble aggregates of kidney bean protein could improve their physicochemical, structural, and emulsifying properties for potential beverage industrial applications. Graphical abstract: Image 1 Highlights: HPH of HKBPs influenced the structure of thermal aggregation denaturation resulting change in emulsifying properties. HPH at low pressure could induce the formation of soluble aggregates proteins. HPH at high pressure could cause disulfide bonds to be broken and disrupt the noncovalent interactions in protein aggregates.